Effect of Cod Liver Oil in the Commercial Feed Cholesterol, Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL) on Meat Fresh Water Prawns (Macrobrachium rosenbergii). - Mega Fitria Ardiany; Agustono .; Boedi Setya Rahardja (Airlangga University, 2017)
Fresh water prawns are commodities freshwater fish that have economic value, particularly in Indonesia. As the development of tourism and a variety of culinary consumption in Indonesia fresh water prawns and open export opportunities. Fresh water prawns, high cholesterol is 385,03 mg/dl. Excessive cholesterol in the body will lead to a condition called atherosclerosis condition is the forerunner of heart disease and stroke. One of the efforts that must be undertaken to produce low cholesterol aquaculture products are engineered feed, supplementation with fatty acids derived from marine organisms. Through the fatty acid supplementation, it is expected that the levels of triglycerides and low density lipoprotein cholesterol (LDL) will decline so it can raise levels of high density lipoprotein cholesterol (HDL). Analysis of data using statistical test of Variant Analysis of variance (ANOVA) to determine the effect of treatment. If there are differences among the treatments continued with Duncan Multiple Range Test to determine the best treatment. Analysis of Variant (ANOVA) result a significant difference (p<0,05). The main parameters of total cholesterol, high density lipoprotein cholesterol (HDL) and low density lipoprotein (LDL) meat prawns tested at the Laboratory of Physiology, Faculty of Medicine, Universitas Brawijaya. Parameter supporters observed that the maintenance of water quality fresh water prawns. Provision of cod liver oil at a dose of 12% can lower total cholesterol with the lowest levels of the other treatments, with an average of 88.3125 mg/dl. Provision of cod liver oil at a dose of 12% can reduce low density lipoprotein (LDL) levels were lowest from other treatments with an average of 197.72 mg/dl. Provision of cod liver oil at a dose of 12% can increase high density lipoprotein (HDL) levels were highest from other treatments with an average of 128.84 mg/dl. Keywords : Cholesterol, Low density lipoprotein (LDL), High density lipoprotein (HDL)